Acute liver dysfunction not resulting from hepatitis virus in immunocompetent children. Issue 5 (21st March 2017) - Tsunoda, Tomoyuki; Inui, Ayano; Iwasawa, Kentaro; Oikawa, Manari; Sogo, Tsuyoshi; Komatsu, Haruki; Ito, Yoshinori; Fujisawa, Tomoo
Abstract: Background: The aim of the present study was to clarify the roles of cytomegalovirus (CMV), Epstein–Barr virus (EBV), and human herpesvirus 6 (HHV‐6) in immunocompetent children with acute liver dysfunction not resulting from hepatitis virus. Methods: Sixty‐eight children (median age, 3 years) hospitalized as a result of acute liver dysfunction were enrolled in this study. Hepatitis A, B, and C were excluded. The prevalence of CMV, EBV, and HHV‐6 and viral DNA load in whole blood was prospectively evaluated on multiplex real‐time polymerase chain reaction (PCR). Results: Of the 68 children with acute liver dysfunction, multiplex real‐time PCR was positive in 30 (44%). CMV, EBV, and HHV‐6 DNA were detected in 13 (19%), 14 (21%), and seven (10%), respectively. Serum CMV immunoglobulin (Ig)G/IgM and EBV viral capsid antigen IgG/IgM were measured in 40 (CMV DNA positive, n = 10; negative, n = 30) and 45 (EBV DNA positive, n = 14; negative, n = 31) of the 68 children, respectively. Eighteen percent (CMV, 7/40) and 9% (EBV, 4/45) were positive for both PCR and viral‐specific IgM. There was no significant difference in CMV and EBV viral load between IgM‐positive and ‐negative children with viremia. Conclusions: CMV, EBV, and HHV‐6 DNA were frequently detected in immunocompetent children with acute liver dysfunction, but primary CMV and EBV infection were confirmed in 10–20% of the children with acute liver dysfunction. The combination of PCR assay and serology is necessary to make a diagnosis of acute liver dysfunction due to primary CMV, EBV and/or HHV‐6 infection in immunocompetent children.